BUNDARAN TUGU KERIS SEBAGAI PUSAT WISATA KULINER KOTA PEKANBARU - Silvy Ocktaviani; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The city of Pekanbaru has many culinary spots which make it as one of the destinations for tourists. One of the culinary spots in Pekanbaru City is Bundaran Keris culinary square. This area has a variety of food and beverages ranging from traditional to modern food. This research aims to describe the Bundaran Keris square in regards to its attractiveness, facilities, accessibility, and institutions. The method used in this research is descriptive qualitative research method. Subjects of this research were the key informants, namely the head of the Pekanbaru City CEI, Pekanbaru City CEI staff, MSME actors, and responses from the visitors at the Bundaran Keris square. Data collection techniques used in this research were observation, interviews, literature study, and documentation. The results showed that the culinary spots in the Bundaran Keris in which where the attractions in the form of food and drinks, food stands, services, and entertainment were good. The facilities provided at the Bundaran Keris are also quite complete, starting from tables and chairs, toilets, mosques, lighting, and parking. The accessibility is also very good pertaining to transportation, road conditions, and pedestrian paths. The institution who has the responsibility to the culinary spots of the Bundaran Keris is the Pekanbaru City Community Empowerment Institute (CEI) which is also the Overseer of the Bundaran Keris culinary spots. Keywords: Culinary Spotsm, Attraction, Pekanbaru City, Bundaran Keris.